The post-mortem vindication of Jesus in the sayings Gospel Q - Smith, Daniel Alan, 1963- (London ; New York : T & T Clark, 2006)
The Sayings Gospel Q, which is conspicuously silent on the issues of Jesus' death and resurrection, nonetheless shows evidence of a knowledge of Jesus' death and of a strategy for accounting for Jesus' vindication. The dissertation argues that Q thinks of Jesus' end as an assumption, a bodily removal from earth to heaven, as happened to figures such as Enoch and Elijah in Jewish tradition. Q 13:34-35, the Jerusalem Lament (Matt 23:37-39 par. Luke 13:34-35), is the central text examined. In this saying, Jesus predicts that "You will not see me until you say, 'Blessed is the Coming One in the name of the Lord'" (Q 13:35b). The language of "not seeing" or disappearance was a consistent feature in Hellenistic assumption narratives, and in Jewish tradition a special eschatological function was typically accorded to those taken away by God in this way. The connection between assumption and eschatological function is seen in Q not only in the reference to the "Coming One" in Q 13:35 (a citation of Ps 118:26), but also in the redactional connections made by Q between materials dealing with an absent master and a suddenly returning Son of man (Q 12:39-40, 12:42b-46; Q 17 'passim' and Q 19). Since Q apparently knows about Jesus' death; yet contains no hint of resurrection theology, the possibility arises that assumption, not resurrection, was how the Q people understood Jesus' vindication by God after his death. The thesis evaluates scholarship on related issues, the death of Jesus in Q and the possibility of an "Easter faith" in Q (Chapter One), and discusses the most significant contributions to the understanding of the Jerusalem Lament as a piece of Q material (Chapter Two). Chapter Three surveys assumption theology in Greco-Roman, Jewish, and early Christian sources. Chapter Four discusses in detail the presence of assumption theology in Q 13:34-35, and Chapter Five investigates the implications of the central thesis for Q as a whole. Finally, other early Christian texts which might betray a similar perspective on Jesus' post-mortem vindication are discussed (Chapter Six).
The death and resurrection of Jesus in Q? -- Q 13.34-35, the Jerusalem lament : survey of research -- Assumption in antiquity -- The death and Assumption of Jesus in Q 13.34-35 -- The significance of Assumption in Q 13.34-35 for other Q materials -- The assumption of Jesus in Q and early Christianity -- Conclusion: Resurrection and/or Assumption : how different is Q?
Includes bibliographical references (p. [173]-192) and indexes.
Keywords: Jesus Christ -- Crucifixion; Jesus Christ -- Resurrection; Bible. -- Criticism, interpretation, etc; Q hypothesis (Synoptics criticism)